Optical Response and Photovoltaic Performance of Organic Solar Cells Based on DH6T:Alq3 Active Layer - Muhammad, Fahmi Fariq; Muhammad, Abdulkader Jaleel; Sulaiman, Khaulah (Journal of Technology Innovations in Renewable Energy, 2016)
This research work reports on the optical and photovoltaic performance of dihexyl-sexithiophene (DH6T) doped with various molar percentages of tris-8-hydroxyquinolinate aluminium (Alq3) dissolved in chloroform/hexane co-solvent. Films of DH6T(1-x)Alq3(x) composite have been produced by casting technique aiming at investigating their absorption edge energies (Eabs) and hence identifying the optimum content of Alq3. It was found that by introducing a controlled amount of Alq3, the value of Eabs can be tuned from 2.69 eV to 1.76 eV. An empirical equation was derived to fit the obtained experimental data, by which an optimum Eabs at molar concentration of (x ≈ 25%) was predicted. Finally, organic solar cells based on the optimum active layer content were fabricated and tested. Comparably, it was observed that the photovoltaic performance of the DH6T:Alq3 based devices is much better than that achieved for the DH6T:PCBM based ones. Efficiency and fill factor for the devices based on DH6T(0.75)Alq3(0.25) active layer were found to be 0.22% and 26.5%, respectively, while those for DH6T:PCBM based devices were about 0.01% and 24%, respectively.